Interactive Learning Video Based on PBL in Pancasila Education Subject for Grade IV Elementary School - Rismayanti, Ni Made; Citra Wibawa, I Made (International Journal of Elementary Education, 2024)
In the current era of globalization, teachers are required to be able to utilize technological advances in the learning process. The lack of utilization of technology in learning causes learning to be less interesting so that student interest in learning drops which has an impact on low student learning outcomes. This study aims to develop interactive learning video media based on problem-based learning material on the implementation of Pancasila values in the era of globalization in the content of Pancasila Education for grade IV elementary school students. This type of research is development research using the ADDIE model. Data collection methods are questionnaires and tests. Data analysis techniques using quantitative descriptive analysis and inferential statistics. The subjects of this study were fourth grade students totaling 34 students. The results of this study indicate that the results of the design expert test obtained a score of 90.60%, the results of the subject content expert test obtained a score of 93.33%, the results of the instructional design expert test obtained a score of 90.62%, the results of the learning media expert test obtained a score of 91.66, the individual trial obtained a score of 96.66%, the small group trial obtained a score of 96.11% with the overall percentage score being in very good qualifications, and the effectiveness results obtained a tcount value of 12.370 for db = 33 and a significance level of 5% obtained a ttable number of 1.692 so that H0 was rejected and H1 was accepted. It can be concluded that interactive learning video media based on problem-based learning is effective and feasible to be applied in the learning process on the implementation of Pancasila values in the era of globalization in the content of Pancasila Education for grade IV elementary school students.